ENVELOPE BROADENING OF OUTGOING WAVES IN 2D RANDOM MEDIA: A COMPARISON BETWEEN THE MARKOV APPROXIMATION AND NUMERICAL SIMULATIONS - Fehler M.; Sato H.; Huang L.J. (My University, 2000)
Observations of seismic waves from earthquakes at depths between 100 and 200 km beneath Japan show that the initial portion of the S-wave arrival has greater duration than can be accounted for by earthquake source-time duration. The observed long duration of S waves has been explained as being caused by multiple forward scattering around the ray path between source and receiver. Array obser- vations of Lg waveforms have also shown that multiple forward scattering along the path between the source and receiver are important influences on the character of Lg waveforms and that the scattering cannot be explained only by vertical variations in velocity. Multiple forward scattering in 3D has been modeled using the Markov approximation for the parabolic-wave equation, which allows the calculation of seis- mogram envelopes in statistically characterized random media. To test the range of validity of the Markov approximation-derived solutions, we made 2D numerical calculations of wavefields in random media using approximations to the parabolic wave equation, which only models forward scattering, and by finite-difference so- lution of the scalar-wave equation, which gives complete wavefields. Media of back- ground velocity 4 km/sec are characterized using a Gaussian autocorrelation function with a5k mcorrelation distance and 5% rms fractional fluctuation. To compare with envelopes obtained from the Markov approximation, we calculated wavefields for source-receiver distances ranging from 50 to 200 km for several statistically identical realizations of random media. We obtain ensemble average envelopes by averaging envelopes from the realizations. We find a good agreement between ensemble- average envelopes obtained from the numerical solution of the parabolic-wave equa- tion and envelopes obtained from the Markov approximation. The later portion of the ensemble-average envelopes calculated using finite difference have larger am- plitudes than those from the Markov approximation, which is probably due to the late-arriving energy that has been scattered at wide angles from the global propa- gation direction between the source and the receiver. We observe that the variations among the numerically calculated envelopes of individual realizations of random media are well fit by a Rayleigh distribution, which describes the distribution of envelope amplitude when signals of one frequency but random phase are summed. Our results show that the Markov approximation provides reliable information about envelope shapes for forward-scattered wavefields but that the influence of wide-angle scattering and backscattering have some influences on envelope shapes and should be considered when analyzing data using random media models.